2011
DOI: 10.1111/j.1475-4754.2011.00603.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Provenance of Lime Plasters From the Templo Mayor of Tenochtitlan (Mexico City)

Abstract: In this work, we present the results of the analyses of 20 lime plaster samples taken from the Templo Mayor (Great Temple), the main pyramid of Tenochtitlan (Mexico), the ancient capital of the Mexicas. The samples were analysed to recover information on the mixtures used in the fabrication of the plasters and for the provenance of the raw materials (in particular, limestone) used to make the plasters. The characterization of the samples was done by OM, SEM/EDS, XRF and LA-ICP-MS analyses, while the identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 25 publications
(49 reference statements)
1
16
0
2
Order By: Relevance
“…A much larger range of archaeological and control samples is needed in order to resolve the geochemical patterns observed in these materials into specific chaînes opératoires. Differences between thin-section observations and bulk geochemical patterns may be resolved in future through more targeted compositional analyses by microprobe analyses of thin sections, which will allow temper to be differentiated from matrix, as Miriello et al (2010Miriello et al ( , 2011a have demonstrated for various archaeological plasters. Nevertheless, we can confirm our field speculations that several different compositional groups were used, and that mudbricks relate to topsoils while most of the plasters and floors were made from imported materials, as signaled by stratigraphic color and texture discontinuities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A much larger range of archaeological and control samples is needed in order to resolve the geochemical patterns observed in these materials into specific chaînes opératoires. Differences between thin-section observations and bulk geochemical patterns may be resolved in future through more targeted compositional analyses by microprobe analyses of thin sections, which will allow temper to be differentiated from matrix, as Miriello et al (2010Miriello et al ( , 2011a have demonstrated for various archaeological plasters. Nevertheless, we can confirm our field speculations that several different compositional groups were used, and that mudbricks relate to topsoils while most of the plasters and floors were made from imported materials, as signaled by stratigraphic color and texture discontinuities.…”
Section: Discussionmentioning
confidence: 99%
“…Outside the Andes, geochemical analyses of construction materials are applied most consistently to lime plasters (e.g., Goren & Goldberg, 1991;Crisci et al, 2004;Barba et al, 2009;Miriello et al, 2010Miriello et al, , 2011aRegev et al, 2010;Gliozzo et al, 2011Gliozzo et al, , 2012Abrams et al, 2012;Bilgen & Olgen, 2012). For instance, Barba et al (2009) combined XRF, laser ablation inductively coupled mass spectroscopy (LA-ICP-MS), and thin-section petrography with scanning electron microscopy energydispersive spectroscopy (SEM-EDS) to assess lime plasters at Teotihuacan.…”
Section: Previous Researchmentioning
confidence: 99%
“…This work is complementary to the work carried out previously on the Templo Mayor's constructive phases, which allowed the characterization of the plasters and the identification of the provenance of the limestone used in the mixtures (Miriello et al . ). This new paper also involves the study of samples from the western stairs of phase VI of the Templo Mayor, which were exposed after the demolition of the Colonial Ajaracas building, allowing the excavation of the area and the exhumation of the last pre‐Hispanic phases of this pyramid.…”
Section: Introductionmentioning
confidence: 97%
“…The aim of this study was to document whether or not there were similarities among the consecutive constructive phases, and whether these similarities could be identified among the different buildings of the Sacred Precinct, including the Templo Mayor that was previously studied (Miriello et al . ). Differences could have been the result of changes in the recipes used for the preparation of plasters (relative proportions or type of raw materials employed) or caused by a diverse provenience of the raw materials.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation